Effect of Knee Arthritis Therapeutic Apparatus on Structure and NF-κB Inflammatory Pathway in Articular Cartilage of Rabbits with Knee Osteoarthritis - Guangwen WU; Jun CHEN; Caibin PAN; Mingxia WU (康复学报)
Objective:To observe the effect of knee arthritis therapeutic apparatus (KATA) on the morphosis of articular cartilage and NF-κB inflammatory pathway in rabbits with knee osteoarthritis (KOA).Methods:24 New Zealand White rabbits were randomly divided into normal group, model group and experiment group, and each group had eight rabbits. The model group and experiment group received modified Hulth's operation to induce KOA model, then the experiment group was treated with KATA for 30 minutes each time, two times per day, and the normal group and model group did not receive any treatment. After 16 weeks, the cartilage morphological changes were observed by HE staining, and the degree of degeneration of cartilage was analyzed according to the Mankin's score, and the positive expression of NF-κB p65, IKK-β and IκB-α were measured by immunohistochemisty.Results:HE staining and Mankin's score showed that the arrangement of articular cartilage structure was improved and cartilage degeneration was reduced in the experiment group. Compared with the model group, the expression of NF-κB p65 and IKK-β were significantly decreased, while IκB-α was significantly increased in the experiment group (P<0.05).Conclusion:KATA could delay cartilage degeneration by regulating the expression of NF-κB inflammatory pathway-related NF-κB p65, IκB-α and IKK-β.